2010
DOI: 10.1007/s11746-010-1629-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Walnut Oils (Juglans regia L.) from Asturias, Spain

Abstract: A total of 15 walnut (Juglans regia L.) samples from 15 cultivars from different geographical areas (Villaviciosa, Colunga, Ribadesella, Llanes, Nava, Peñamellera and Sariego) from Asturias, Spain were studied. Samples of virgin walnut oil were obtained from dehusked ground walnuts by extraction at a pressure of 160 kg cm -2 and temperature below 40°C for 3 min. The oil obtained by pressure was filtered for analysis. Fatty acid, sterol and tocopherol compositions as determined by capillary column gas chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
39
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 14 publications
14
39
3
Order By: Relevance
“…The mean value over the two years ranged between 188.1 and 230.7 mg·kg −1 oil for γ-tocopherol (Table 3). This range agreed with previous results (Amaral et al, 2005), but the maximum values of the Moroccan seedlings were lower than those previously reported (Savage et al, 1999;Bada et al, 2010). The concentration of δ-tocopherol ranged from 23.3 to 43.4 mg·kg −1 oil (Table 3), higher than in a previous report (Amaral et al, 2005), but lower than in others (Savage et al, 1999;Bada et al, 2010).…”
Section: Tocopherol Concentrationsupporting
confidence: 91%
See 4 more Smart Citations
“…The mean value over the two years ranged between 188.1 and 230.7 mg·kg −1 oil for γ-tocopherol (Table 3). This range agreed with previous results (Amaral et al, 2005), but the maximum values of the Moroccan seedlings were lower than those previously reported (Savage et al, 1999;Bada et al, 2010). The concentration of δ-tocopherol ranged from 23.3 to 43.4 mg·kg −1 oil (Table 3), higher than in a previous report (Amaral et al, 2005), but lower than in others (Savage et al, 1999;Bada et al, 2010).…”
Section: Tocopherol Concentrationsupporting
confidence: 91%
“…Oil content ranged between 54.4 and 67.48%, and protein between 11.58 and 14.5% in 2009, (Table 1), whereas in 2010 these ranges were between 55.29 and 66.25% for oil, and between 11.99% and 14% for protein (Table 1). Protein content agreed with previous reports (Amaral et al, 2003;Savage et al, 1999), as well as fat content, although the lowest fat value was lower than any previous report (Crews et al, 2005;Amaral et al, 2003;Martinez et al, 2006;Bada et al, 2010). The significance of the year×genotype interaction (Table 2) indicated that oil content variability was significant between years for some genotypes, as a result of the specific response by these genotypes to the environmental conditions of the year.…”
Section: Oil and Protein Contentsupporting
confidence: 89%
See 3 more Smart Citations